Candidate Genes for Nonsyndromic Cleft Palate Detected by Exome Sequencing. (October 2017) - Hoebel, A.K.; Drichel, D.; van de Vorst, M.; Böhmer, A.C.; Sivalingam, S.; Ishorst, N.; Klamt, J.; Gölz, L.; Alblas, M.; Maaser, A.; Keppler, K.; Zink, A.M.; et al.
Nonsyndromic cleft palate only (nsCPO) is a facial malformation that has a livebirth prevalence of 1 in 2, 500. Research suggests that the etiology of nsCPO is multifactorial, with a clear genetic component. To date, genome-wide association studies have identified only 1 conclusive common variant for nsCPO, that is, a missense variant in the gene grainyhead-like-3 ( GRHL3 ). Thus, the underlying genetic causes of nsCPO remain largely unknown. The present study aimed at identifying rare variants that might contribute to nsCPO risk, via whole-exome sequencing (WES), in multiply affected Central European nsCPO pedigrees. WES was performed in 2 affected first-degree relatives from each family. Variants shared between both individuals were analyzed for their potential deleterious nature and a low frequency in the general population. Genes carrying promising variants were annotated for 1) reported associations with facial development, 2) multiple occurrence of variants, and 3) expression in mouse embryonic palatal shelves. This strategy resulted in the identification of a set of 26 candidate genes that were resequenced in 132 independent nsCPO cases and 623 independent controls of 2 different ethnicities, using molecular inversion probes. No rare loss-of-function mutation was identified in either WES or resequencing step. However, we identified 2 or more missense variants predicted to be deleterious in each of 3 genes ( ACACB, PTPRS, MIB1 ) in individuals from independent families. In addition, the analyses identified a novel variant in GRHL3 in 1 patient and a variant in CREBBP in 2 siblings. Both genes underlie different syndromic forms of CPO. A plausible hypothesis is that the apparently nonsyndromic clefts in these 3 patients might represent hypomorphic forms of the respective syndromes. In summary, the present study identified rare variants that might contribute to nsCPO risk and suggests candidate genes for further investigation.